2014
DOI: 10.1097/iae.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraocular Lens Power Estimation in Eyes Having Phacovitrectomy for Rhegmatogenous Retinal Detachment

Abstract: Summary Statement:Combined phacovitrectomy as primary repair surgery for rhegmatogenous retinal detachment (RRD) included a small biometric error that was within the tolerable range in most cases.The biometry used for IOL power selection must be checked by comparing with the fellow eye and the known refraction, especially in macula-off RRD cases. 3ABSTRACT PURPOSE: To evaluate the accuracy of intraocular lens (IOL) power estimation in eyes having phacovitrectomy for rhegmatogenous retinal detachment (RRD).METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 24 publications
5
55
0
2
Order By: Relevance
“…Our previous large case series study has shown the refractive results of phacovitrectomy for RRD to be comparable with cataract surgery outcomes. 1 Overall, although optical biometry (OB) was more accurate than ultrasound (US) (p=0.040), we noted that significantly more US measured ALs were preferentially selected over OB measurements in the macula-off group compared to macula-on group (p=0.016). We concluded that the biometry used for IOL power selection must be checked by comparing with the fellow eye and the known refraction, especially in macula-off RRD cases.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our previous large case series study has shown the refractive results of phacovitrectomy for RRD to be comparable with cataract surgery outcomes. 1 Overall, although optical biometry (OB) was more accurate than ultrasound (US) (p=0.040), we noted that significantly more US measured ALs were preferentially selected over OB measurements in the macula-off group compared to macula-on group (p=0.016). We concluded that the biometry used for IOL power selection must be checked by comparing with the fellow eye and the known refraction, especially in macula-off RRD cases.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have shown that OB is more accurate than US in general [10][11][12][13] , except in macula-off cases where the accuracy of primary OB measurements have to be assessed with caution by careful comparison to the known refraction and AL of the fellow-eye 1 . In the macula-off group of our previous study, significantly more US measured ALs were preferentially selected for IOL power estimation instead of primary OB measurements 1 . The current study however shows that mean pre-operative AL values derived from user-adjusted OB indicate no evidence for a statistically significant difference from AL values derived from US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables better and faster visual recovery in comparison with isolated vitrectomy [14] and saves a second procedure, which is, furthermore, more complicated in the case of vitrectomised eyes [15,16,17,18]. In contrast to other authors [19], we excluded cases with retinal detachment from any cause since the postoperative incidence of complications is greater, with the formation of proliferative vitreoretinopathy or synechiae in the anterior segment [18,20] (as in 1 of the cases presented in our series) and difficulty in calculating the power of the IOL when there is an associated scleral procedure [21], and IOL stability. …”
Section: Discussionmentioning
confidence: 86%
“…Scenario 1: A study to evaluate the accuracy of intraocular lens power estimation in eyes having phacovitrectomy for rhegmatogenous retinal detachment4 measured the axial length (in mm) of 71 eyes. The raw data (figure 1A) exhibited a fairly strong positive skew (rather than being symmetric there is an extended tail in the histogram to the right); the same data with a logarithmic transformation applied (figure 1B) appears much more normal (less of a tail to the right), and hence the power of a test conducted on transformed data should be greater.…”
Section: Introductionmentioning
confidence: 99%